Students’ Writing Ability In Writing Procedure Text By Using Image Media - Diana Eva Lux Putri; Aulia Rahmadani; Indah Budiarti; Mudmainnah (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2025)
Writing activities are not only a way to record ideas, but also function as a medium for developing critical, systematic, and creative thinking skills. Using thinking skills (critical, systematic, creative) by using image media to develop thinking skills presented by visual stimuli. This study aimed to analyze students’ writing ability in procedure text by using media at seventh grade students of MTs Miftahul Huda Tasik Serai. This research used quantitative approach which using descriptive research design. To compile the procedure text in order and logically, students must first understand the stage by stage to be done, and the media images greatly help students’ understanding in compiling the text procedure. The collecting data by using writing test to write procedure text. The total sample was 18 respondents, excellent category was 5.56%, very good category was 27.78% , 50% was good category, and fair category was 16.67 %. It showed that the students have understood the basics of writing procedure text, such as structure and sequence of steps. However, there are still 16.67% of students who have not shown adequate writing skills. This research showed the students’ writing ability is at a good level. However, future instructional emphasis should be directed at improving writing coherence for the majority group and providing intensive writing for those falling below the passing threshold.